Base material for screw, screw, and method for producing the same
Patent Information
- Application Number
- JP2024044224
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-07
- Filing Date
- 2024-03-19
- Publication Date
- 2025-03-18
AI Technical Summary
Pure titanium screws lack sufficient tensile and torsional rupture strength for medical applications, and conventional methods to enhance strength, such as work hardening and micro-strengthening, are not sufficient for stable and reliable mass production.
A method involving swaging of commercially available pure titanium bars or wires to achieve a maximum specific strength of the (1 0 -1 0) plane orientation of 3 or more, with a crystallite size of 280 Å or less, and possessing characteristics like tensile strength of 800 MPa or more, hardness of 200 HV or more, and aperture of 45% or more, without requiring special processes.
The method produces a pure titanium screw base material with strength comparable to titanium alloys, suitable for medical applications, enabling stable and reliable production at lower costs by avoiding complex processes.
Smart Images

Figure 00000016_0000 
Figure 00000016_0001 
Figure 00000016_0002
Abstract
Description
[Technical field]
[0001] The present invention relates to a base material for a screw or a screw and a manufacturing method thereof, in particular a base material for a medical screw or a medical screw and a manufacturing method thereof, more particularly a base material for a medical anchor screw or a medical anchor screw and a manufacturing method thereof, and further particularly a base material for an anchor screw for orthodontics or an anchor screw for orthodontics and a manufacturing method thereof. [Background technology]
[0002] Titanium medical screws have become important in medical implants. Most of them are made of alloy titanium (Ti64). Titanium alloys (e.g. Ti-6Al-4V) have had allergy problems due to the alloying elements, especially vanadium.
[0003] Also, in industrial products, for example in the semiconductor industry, in the substrate cleaning process using special acids and solutions that require cleanliness and corrosion resistance, and in the film formation process exposed to vacuum or special gas environments, titanium alloys, such as Ti-6Al-4V, are not only inferior in corrosion resistance to pure titanium, but also cause the elution of added elements aluminum and vanadium, which can cause impurities to be mixed in, so titanium alloys cannot be used and pure titanium screws are used. On the other hand, pure titanium has low strength, so the lack of strength is compensated for by increasing the size of the screw or the number of screws, and there is a demand for improving the strength of the pure titanium itself.
[0004] As a method for improving the strength of pure titanium, for example, Patent Documents 1 and 2 show that mechanical properties are improved by swaging titanium or titanium alloys as implants. Patent Document 3 also shows appropriate processing conditions and processing degrees. However, Patent Documents 1 to 3 show the advantages of general processing strengthening common to plastic processing of metals, and it is preferable that the processing degree is 20 to 80%, and it is shown that if it is more than 80%, it becomes brittle and cracks occur during processing.
[0005] Furthermore, although Patent Document 4 discloses details regarding the characteristics of the processing style of swaging, this information is merely qualitative and cannot be said to be sufficient in terms of reliability. Patent Document 5 shows a technique for improving the mechanical properties of titanium by methods such as warm rolling, extrusion, and die forging. This technique uses an enhanced crystal grain refinement strengthening method called Enhanced Cyclic Shear Processing (ECAP), which produces a material by controlling the temperature while heating it from the surroundings, and then enhances the effect by rolling, which is the main secondary processing. It is particularly characterized by refinement and improved crystal isotropy.
[0006] Patent Document 6 also shows that titanium can be refined by multi-axis forging (MDF), and then rolled and processed into a wire shape, and that the strength can be increased by keeping the processing temperature at 70°C or less. Furthermore, Non-Patent Document 1 discloses that for pure titanium types 1 to 4, the starting material is refined through structural changes caused by heat treatment such as quenching, and then further strengthened by processing. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] FY2014 Research Results Report (Kyoto Institute of Technology) Hiroaki Matsumoto: New ultrafine grain structure formation in lightweight pure titanium material and new developments in high performance and practical plastic processing. [Patent documents]
[0008] [Patent Document 1] Patent Publication No. 7-124242. [Patent Document 2] Patent Publication No. 9-135852. [Patent Document 3] Patent Publication No. 7-124242. [Patent Document 4] Patent Publication No. 9-135852. [Patent Document 5] Patent No. 5536789. [Patent Document 6] Patent No. 6737686. Summary of the Invention [Problem to be solved by the invention]
[0009] Pure titanium is the metal with the least risk of allergies, but compared to alloy titanium, it lacks the tensile strength and torsional breaking strength required for medical screws. Since minimal invasiveness is required, increasing the size to increase strength is not desirable, and the material itself needs to be strong. Conventional technology has attempted to utilize the work hardening and fine strengthening properties of pure titanium to improve its mechanical properties, but this has not been sufficient, and more recently, special materials have been made finely strengthened by massive plastic deformation (UFG, bulk ultrafine grained), which is then rolled to create cylindrical shapes (bar material or wire material) for medical screws. This makes the process complicated, and there are restrictions on the shape and volume of the massive plastic deformation processed material, making it unsuitable for actual mass production, and a low-cost, highly productive method has been sought.
[0010] Meanwhile, commercially pure titanium (CP titanium), which is sold commercially as bar material or wire material, is easily available, but its crystal grains are large, at several tens of microns in size, and its strength is insufficient, and its internal structure varies somewhat. Therefore, even when using this material, quality control is required to ensure stable production and high reliability.
[0011] Therefore, an object of the present invention is to provide a pure titanium screw base material or a pure titanium screw, particularly a medical screw base material or a medical screw, more particularly a medical anchor screw base material or a medical anchor screw, and even more particularly an orthodontic anchor screw base material or an orthodontic anchor screw, which have sufficient strength comparable to that of a titanium alloy.
[0012] Another object of the present invention is to provide a method for producing the pure titanium screw base material or the pure titanium screw, etc., other than or in addition to the above object. Specifically, an object of the present invention is to provide a manufacturing method that can manufacture the above-mentioned pure titanium screw base material or pure titanium screw, etc., from commercially available pure titanium bar material or wire material without undergoing a special process such as massive strain processing, and that can manufacture the above-mentioned pure titanium screw base material or pure titanium screw, etc., using a stable and highly reliable management method in terms of production. [Means for solving the problem]
[0013] The present inventors have discovered the following invention. <1> A screw base material or screw made of pure titanium having a substantially cylindrical shape, the maximum value of the specific intensity of the orientation of the (1 0 -1 0) plane in the axial direction of the substantially cylindrical shape being 3 or more, preferably 4 or more, and more preferably 5 or more. For the term "(1 0 -1 0) plane", see below. <2> the above <1> In the above, the crystallite size of the pure titanium is preferably 280 Å or less, more preferably 270 Å or less, and even more preferably 260 Å or less.
[0014] <3> the above <1> or <2> In the above, the screw base material or the screw preferably has at least one, two, or three of the following characteristics i) to iii). Property i): tensile strength of 800 MPa or more, preferably 860 MPa or more, more preferably 920 MPa or more; Property ii): hardness of 200HV or more, preferably 220HV or more, more preferably 240HV or more; Characteristic iii): Reduction of area is 45% or more, preferably 50% or more, and more preferably 60% or more.
[0015] <4> A screw base material or screw made of pure titanium, the crystallite size of the pure titanium being 280 Å or less, preferably 270 Å or less, more preferably 260 Å or less, and having at least one, two, or three of the following properties i) to iii): Property i): tensile strength of 800 MPa or more, preferably 860 MPa or more, more preferably 920 MPa or more; Property ii): hardness of 200HV or more, preferably 220HV or more, more preferably 240HV or more; Characteristic iii): Reduction of area is 45% or more, preferably 50% or more, and more preferably 60% or more.
[0016] <5> the above <1> ~ <4> In any one of the above, the pure titanium is preferably selected from the group consisting of pure titanium type 2, pure titanium type 3, pure titanium type 4, and pure titanium whose crystal grains have been refined to 1 μm or less. <6> the above <1> ~ <5> In any one of the above, the pure titanium is preferably type 4 pure titanium.
[0017] <7> the above <1> ~ <6> In any one of the above, the screw base material or the screw may be a medical anchor screw base material or a medical anchor screw. <8> the above <1> ~ <7> In any one of the above, the screw base material or the screw may be a base material for an anchor screw for orthodontics or an anchor screw for orthodontics.
[0018] <9> (I) preparing a generally cylindrical pure titanium material having a cross-sectional area of A0; and (II) swaging the pure titanium material; By having the above structure, a substantially cylindrical screw base material is obtained having a cross-sectional area of A1 after swaging and a true strain expressed as ln(A0 / A1) of 2 or more.
[0019] <10> (I) preparing a generally cylindrical pure titanium material having a cross-sectional area A0; and (II) swaging the pure titanium material; By having the above, a substantially cylindrical screw base material is obtained, the cross-sectional area after swaging is A1, and the true strain expressed by ln(A0 / A1) is 2 or more, (III) a step of imparting a screw shape to the substantially cylindrical screw base material; The method for producing a screw includes the steps of:
[0020] <11> the above <1> ~ <8> The screw base material according to any one of the preceding claims or <9> 2. A method for manufacturing a screw, comprising the step of forming a screw head by pressing the screw base material obtained by the manufacturing method described in claim 1 at 250° C. or less.
[0021] <12> the above <10> In the method, it is preferable to further include a step of forming the screw head by pressing the screw base material at 250°C or less after the step (II), or to further include a step of forming the screw head by pressing the screw at 250°C or less after the step (III).
[0022] <13> the above <9> ~ <12> In any of the above, the approximately cylindrical screw base material or the approximately cylindrical screw has a maximum specific intensity of the orientation of the (1 0 -1 0) plane in its axial direction of 3 or more, preferably 4, and more preferably 5. <14> the above <9> ~ <13> In any one of the above, the crystallite size of the pure titanium material is 280 Å or less, preferably 270 Å or less, and more preferably 260 Å or less. <15> the above <9> ~ <14> In any of the above, the substantially cylindrical screw base material or the substantially cylindrical screw is made of pure titanium, and the crystallite size is 280 Å or less, preferably 270 Å or less, and more preferably 260 Å or less.
[0023] <16> the above <9> ~ <15> In any one of the above, the substantially cylindrical screw base material or screw preferably has at least one of the following characteristics i) to iii). Property i): tensile strength of 800 MPa or more, preferably 860 MPa or more, more preferably 920 MPa or more; Property ii): hardness of 200HV or more, preferably 220HV or more, more preferably 240HV or more; Characteristic iii): Reduction of area is 45% or more, preferably 50% or more, and more preferably 60% or more.
[0024] <17> the above <9> ~ <16> In any one of the above, the pure titanium material is preferably selected from the group consisting of pure titanium type 2, pure titanium type 3, pure titanium type 4, and pure titanium whose crystal grains have been refined to 1 μm or less. <18> the above <9> ~ <17> In any of the above, the pure titanium material is preferably type 4 pure titanium.
[0025] <19> the above <9> ~ <18> In any one of the above, the screw base material or the screw may be a medical anchor screw base material or a medical anchor screw. <20> the above <9> ~ <19> In any one of the above, the screw base material or the screw may be a base material for an anchor screw for orthodontics or an anchor screw for orthodontics. Effect of the Invention
[0026] According to the present invention, it is possible to provide a pure titanium screw base material or a pure titanium screw, particularly a medical screw base material or medical screw, more particularly a medical anchor screw base material or medical anchor screw, and even more particularly an orthodontic anchor screw base material or orthodontic anchor screw, having sufficient strength comparable to that of a titanium alloy. Furthermore, according to the present invention, in addition to or in addition to the above-mentioned effects, it is possible to provide a method for manufacturing the pure titanium screw base material or the pure titanium screw, etc. Specifically, the present invention can provide a manufacturing method that can manufacture the above-mentioned pure titanium screw base material or pure titanium screw, etc. from commercially available pure titanium bar material or wire material without undergoing a special process such as massive strain processing, and that can manufacture the above-mentioned pure titanium screw base material or pure titanium screw, etc., using a stable and highly reliable management method in terms of production. [Brief description of the drawings]
[0027] [Figure 1] Pure titanium type 2 (CP-T2), pure titanium type 4 (CP-T4), and FTi2 materials were prepared with true strains of 0, 2.0, and 3.7. The (1 0 -1 0) plane of the rod-shaped processed base materials of the examples was represented as a pole figure using the analysis software DIFFRAC.TEXTURE MRDB V4.1 (manufactured by BRUKER). [Diagram 2] FIG. 2 is a graph showing the crystallite size (Å) on the horizontal axis and the tensile strength (MPa) on the vertical axis for the rod-shaped preform obtained in the examples. [Diagram 3] FIG. 2 is a graph showing the crystallite size (Å) on the horizontal axis and the hardness (HV) on the vertical axis for the rod-shaped processed base material obtained in the examples. [Figure 4]FIG. 1 is a graph showing the crystallite size (Å) on the horizontal axis and the reduction in area (%) on the vertical axis for the rod-shaped processed base material obtained in the examples. [Diagram 5] FIG. 2 is a graph showing true strain ε on the horizontal axis and crystallite size (Å) on the vertical axis for the rod-shaped processed base material obtained in the examples. [Figure 6] 1 is a graph showing true strain ε on the horizontal axis and maximum specific strength (orientation) on the vertical axis for the rod-shaped processed base material obtained in the examples. [Figure 7] FIG. 2 is a graph showing the maximum specific strength (orientation) on the horizontal axis and the tensile strength (MPa) on the vertical axis for the rod-shaped base material obtained in the examples. [Figure 8] FIG. 2 is a graph showing maximum specific strength (orientation) on the horizontal axis and hardness (HV) on the vertical axis for the rod-shaped processed base material obtained in the examples. [Figure 9] FIG. 1 is a graph showing the maximum specific strength (orientation) on the horizontal axis and the reduction in area (%) on the vertical axis for the rod-shaped preform obtained in the examples. [Figure 10] This is a graph showing true strain ε on the horizontal axis and reduction in area (%) on the vertical axis for the base material obtained using material CP-T4. [Figure 11] This is a photograph of the heads after processing the base material CP-T4 obtained with a true strain of 0 and a true strain of 2.65. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The invention described in this application (hereinafter sometimes abbreviated as "the present invention") will be described below. The present application provides a substantially cylindrical pure titanium screw base material, a substantially cylindrical pure titanium screw, a method for manufacturing the screw base material, and a method for manufacturing the screw. Each of these will be explained in turn below. <Screw base material> The present application provides a substantially cylindrical pure titanium screw base material, in which the maximum specific strength of the orientation of the (1 0 -1 0) plane in the axial direction of the substantially cylindrical screw base material is 3 or more, preferably 4 or more, and more preferably 5 or more. In addition, the maximum specific strength of the orientation is 15 or less, preferably 12 or less, and more preferably 10 or less. In addition, the phrase "(1 0 -1 0)" in this specification is usually expressed as (X) below. However, for the sake of convenience, the phrase "(1 0 -1 0)" will be used in this specification.
[0029]
number
[0030] In the case of a screw base material, the term "approximately cylindrical" not only includes a cylindrical shape, but also a so-called truncated cone shape in which the side surface is inclined along the axial direction of the cylinder. "Made of pure titanium" does not only mean titanium that does not contain any impurities, but also titanium type 1, type 2, type 3, or type 4 according to the JIS standard, or pure titanium with crystal grains refined to 1 μm or less. The material of "pure titanium" is preferably selected from the group consisting of pure titanium type 2, pure titanium type 3, pure titanium type 4, and pure titanium with crystal grains refined to 1 μm or less.
[0031] <Orientation of the (1 0 -1 0) plane in the axial direction> In the screw base material of the present invention, the maximum value of the specific orientation strength of the (1 0 -1 0) plane in the axial direction of the substantially cylindrical shape is 3 or more. Moreover, the maximum value is preferably 4 or more, more preferably 5 or more. Moreover, the maximum value of the specific orientation strength is 15 or less, preferably 12 or less, more preferably 10 or less. Here, the term "axial direction" is synonymous with the length direction of a substantially cylindrical shape. Pure titanium is usually isotropic (or equiaxed crystal), but it can be given orientation by processing. This orientation can give the screw base material properties that cannot be obtained with an isotropic (or equiaxed crystal) structure. A specific crystal plane is preferentially arranged in the axial direction by applying a force perpendicular to the outer circumferential surface of the raw material material to the center of the material to obtain a roughly cylindrical screw base material with a circular cross section. This generally increases the strength in the axial direction, and can improve the tensile strength of the screw base material and the screw formed from the base material.
[0032] Although the orientation of pure titanium is a fundamental characteristic along with the crystallites, it has not been quantitatively treated, but rather has been treated as a qualitative factor that affects the mechanical properties. In order to quantitatively evaluate this orientation, we used X-ray diffraction (XRD) and discovered that it can be quantitatively treated by the maximum ratio of intensity to the average intensity for a specific crystal plane of pure titanium in the direction of interest.
[0033] In other words, we created a pole figure for the characteristic crystal plane (1 0 -1 0) of pure titanium, which is a close-packed hexagonal crystal, in the direction perpendicular to the cross section of the roughly cylindrical material (axial direction), and calculated the maximum specific intensity within that. This is the "maximum value of the specific intensity of the orientation of the (1 0 -1 0) plane in the axial direction of the roughly cylindrical shape."
[0034] A pole figure shows how a particular crystal plane of a material is distributed in a cross section of the material, and its intensity is generally shown as a contour diagram or shaded area. The ratio of the intensity of the darkest part to the average is the maximum specific intensity. The higher the specific intensity, the greater the orientation (also called anisotropy), and the closer it is to 1, the less orientation there is, and the distribution is isotropic or random.
[0035] The maximum value of the specific intensity can be obtained by using X-ray diffraction (XRD) as described above. Specifically, the X-ray diffraction device used was a BRUKER D8 ADVANCE, the tube was cobalt, and the output was set to a voltage of 35 kV and a current of 40 mA. A two-dimensional detector was used with a divergence slit diameter of 0.3 mm and a collimator diameter of 0.3 mm.
[0036] In creating the pole figures, the in-plane direction angle Φ of the sample was measured in 72 steps at 5 degree intervals around 360 degrees, and the range of the tilt angle Ψ was measured with a starting point of 15 degrees and an end point of 45 degrees. The obtained measurement data was analyzed using the analysis software DIFFRAC.TEXTURE MRDB V4.1 (manufactured by BRUKER) to create pole figures of (1 0 -1 0) that show characteristic behavior in the orientation of pure titanium. This allows the direction in which the crystal plane is most likely to face to be determined by the color intensity. The maximum value of the relative intensity, with the average intensity of the entire pole figure set to 1, is the maximum specific intensity. When the material is isotropic (no orientation), there is little color shading, and when orientation appears, a dark area appears at a certain angle, and the relative intensity of that angle becomes high. The angle at which this intensity is maximum can also be found using a contour map.
[0037] In the present invention, as described above, the "maximum value of the specific intensity of the orientation of the (1 0 -1 0) plane in the axial direction of the approximately cylindrical shape" is 3 or more, preferably 4 or more, and more preferably 5 or more.
[0038] <Mechanical properties> Screws, particularly for medical use, require high strength and high toughness. These properties are also required for the base material for the screw. Regarding strength, the tensile strength in the axial direction of the screw, that is, in the axial direction of the screw base material, is important. The tensile strength is preferably 800 MPa or more, more preferably 860 MPa or more, and even more preferably 920 MPa or more. To approximate the strength of titanium alloys (e.g., Ti-6%Al-4%V), the strength is preferably 820 MPa or more. Depending on the application, 950 MPa is even more preferable. The tensile strength can be measured by an Amsler universal testing machine.
[0039] Furthermore, when screws, particularly medical screws, are screwed in, a torsional shear strength is required, and the torsional shear strength is roughly proportional to the hardness of the material. Therefore, the Vickers hardness is preferably 200 HV or more, more preferably 220 HV or more, and even more preferably 240 HV or more. The hardness can be measured by a Vickers hardness tester.
[0040] Furthermore, the screw must have high toughness (not be brittle) and is generally required to have a sufficient necking at the time of break, i.e., to have a reduction in diameter. Therefore, the reduction is 45% or more, preferably 50% or more, and taking into consideration the subsequent processability, for example, heading ability, it is more preferably 60% or more. In this specification, the term "drawing" refers to plastic workability in the axial direction (length direction) of a substantially cylindrical shape. The reduction in area can be measured based on an evaluation value of the necking at the time of tensile break, and specifically, the reduction in area can be tested and measured by an Amsler type universal testing machine.
[0041] <Crystallite size> In order to create a structure suitable for screws, especially medical screws, and to ensure the reliability of the actual product, the evaluation method is important. However, this phenomenon in pure titanium is a very complicated phenomenon involving recrystallization, accumulation of strain, twin crystals, etc. Therefore, since the crystal grains themselves are complicated, it is difficult to use conventional evaluation methods, such as measurement and evaluation with an optical microscope, and even when determining the grain size with a transmission X-ray device, complicated procedures such as setting the angle (tilt angle) between adjacent crystals are required. In addition, this method is not easily suitable as an inspection and evaluation method for the production process.
[0042] Therefore, it was found that by using the crystallite size that exists as an original crystal unit among complex crystal grains, an effective index can be given to the above-mentioned complex structure, and by using this appropriately, the target screw, particularly a medical screw, can have the desired mechanical properties.
[0043] A crystallite is different from the crystal grain size and is the smallest unit that contributes to X-ray diffraction, and is the part of a crystal grain that can be regarded as a single crystal. The crystallite size is different from the crystal grain size, which is determined from the apparent size of the crystal, and is a smaller value (or unit) than that. In addition, in a pure single crystal, the crystal grain size and the crystallite size can be considered to be almost the same, but when processing is added and the crystal loses its regularity under various conditions, they do not necessarily correlate with the crystal grain size. It was decided to use the crystallite size as an indicator of whether pure titanium has desired properties, particularly mechanical properties, regardless of whether it has been processed or not and the degree of processing.
[0044] The crystallite size can be identified by an X-ray diffraction (XRD) device, and can also be used as a manufacturing process inspection. Specifically, the crystallite size can be measured as follows. The X-ray diffraction apparatus used was a BRUKER D8 ADVANCE, and the cobalt Kα X-rays were used. The output of the cobalt tube was 35 kV and the current was 40 mA. In this specification, the crystallite size is determined by measuring the diffracted X-rays of the crystal plane (1 0 -1 0) of pure titanium. The X-ray scanning range is 2θ=35.0°~48.0°, the divergence slit diameter is 0.3 mm, and the collimator diameter is 0.3 mm. The measurement data is analyzed using the company's analysis software DIFFRAC.EVA. The crystallite size is L vol [Å], the measurement wavelength λ [Å], the integral width of the peak excluding the influence of the instrument β [rad], the angular position of the peak θ [rad], and the crystallite size L volcan be calculated from the Scherrer equation shown in Equation 1.
[0045]
number
[0046] For details on crystallite size, see Waseda, Matsubara, and Shinoda (2008) Fundamentals of X-ray Structure Analysis (Uchida, Rokakuho), pp. 103-108 (all of which are incorporated herein by reference).
[0047] In the present invention, the crystallite size is 280 Å or less, preferably 270 Å or less, and more preferably 260 Å or less.
[0048] <Screw> The screw of the present invention may be formed from the above-mentioned screw base material, and therefore may have the same characteristics as the above-mentioned screw base material. In other words, the screw of the present invention is a generally cylindrical screw made of pure titanium, and the maximum specific intensity of the orientation of the (1 0 -1 0) plane in the axial direction of the generally cylindrical shape is 3 or more, preferably 4 or more, and more preferably 5 or more. The crystallite size of the pure titanium is preferably 280 Å or less, more preferably 270 Å or less, and even more preferably 260 Å or less.
[0049] Furthermore, it is preferable that the material has at least one, two, or three of the following mechanical properties i) to iii). Property i): tensile strength of 800 MPa or more, preferably 860 MPa or more, more preferably 920 MPa or more; Property ii): hardness of 200HV or more, preferably 220HV or more, more preferably 240HV or more; Characteristic iii): Reduction of area is 45% or more, preferably 50% or more, and more preferably 60% or more.
[0050] The screw of the present invention is made of pure titanium, and specifically, the pure titanium is selected from the group consisting of pure titanium type 2, pure titanium type 3, pure titanium type 4, and pure titanium having crystal grains refined to 1 μm or less, and preferably pure titanium type 4.
[0051] Furthermore, the screw of the present invention may have a combination of A) a desired maximum value of the specific strength of the orientation and B) a desired crystallite size. Alternatively, the screw of the present invention may have a combination of B) a desired crystallite size and C) at least one, two, or three of the mechanical properties i) to iii). Alternatively, the screw of the present invention may have a combination of A) a desired maximum value of the specific strength of the orientation, B) a desired crystallite size, and C) at least one, two, or three of the mechanical properties i) to iii).
[0052] The screw base material of the present invention is preferably a base material for a medical screw, particularly a base material for a medical anchor screw. The base material for a medical anchor screw is preferably a base material for an anchor screw for dental orthodontics. The screw of the present invention is preferably a medical screw, particularly a medical anchor screw. The medical anchor screw is preferably an anchor screw for dental orthodontics.
[0053] <Method of manufacturing base material for screws> The above-mentioned screw base material can be produced by the following production method. That is, (Ia) preparing a pure titanium material; and (IIa) swaging the pure titanium material; By having the above-mentioned structure, the screw base material can be obtained.
[0054] Here, "swaging" is adopted as the processing method for pure titanium, and the reasons for adopting it are as follows. In other words, when metal materials are deformed (plastic deformation), about 90% of the strain energy introduced by the deformation is converted into heat (processing heat), raising their own temperature. Generally, this is thought to be around 100°C, depending on the processing method, and processing is not done using only the heat generated during processing; conversely, processing is done by cooling the mold to suppress the disadvantages of heat.
[0055] Titanium has a low thermal conductivity, which limits the diffusion of heat throughout the material, and the heat remains in the part of the material that is plastically deformed, causing the temperature to rise even more. If the processing conditions are the same, titanium's thermal conductivity is less than half that of steel, so it is expected that the temperature of the processed part will rise by about twice as much, or about 200°C.
[0056] Furthermore, by increasing the processing speed (or strain rate), the process enters the high-speed processing region above a certain speed, and a large amount of heat can be generated locally by a mechanism different from the processing heat mentioned above. For example, in swaging, the high-speed rotation of the outer rollers can be used, making it possible to achieve a surface collision processing speed of approximately 50 meters per second. The strain rate at that time is approximately 10 to 100 / s, which is almost within the high-speed processing region.
[0057] If the contact time between the die and the titanium material is instantaneous, there will be almost no heat flow to the die, and the heat will be trapped within the material. Because swaging has these characteristics, it is a favorable processing method for raising the temperature of the material itself using processing heat.
[0058] In this way, by combining titanium's low thermal conductivity with high-speed processing, it is possible to heat the material to over 300°C without heating it from the surroundings. Specifically, by appropriately setting the rotation speed for high-speed processing, the insertion speed of the material to be processed, the contact time with the die, the amount of lubricant applied, the processing rate per process (the processing rate of a single process), and the total processing rate (the sum of the processing rates of the single processes), it is possible to control the strain rate while maintaining the internal temperature of the material at 300-400°C. This makes it possible to create an appropriate balance (equilibrium state) between the introduction of processing strain and the generation of recrystallization.
[0059] In this way, by utilizing the processing heat of the material itself, it is possible to control the crystal state and its orientation, and thus the strength and toughness of the material can be controlled, forming a structure appropriate for the screw and providing the above-mentioned characteristics.
[0060] According to this method, it is possible to continue processing without intermediate annealing (softening heat treatment to give ductility to the material), and the material diameter can be reduced by repeating the single process several to several tens of times to process it to the final material diameter. In this way, the ductility is improved spontaneously by recrystallization that occurs during processing, so it is possible to achieve a total processing degree (sum of single processes) of 80 to 95% or more, exceeding conventional cases.
[0061] Since it is possible to achieve an extremely large total degree of processing, it is now possible to absorb variations in the structural state of the material before processing. By using this method, it is possible to impart sufficient properties to medical screws using standard commercially pure titanium bar or wire materials of types 1 to 4, without using finely-fine materials as the raw material, for example materials made by cyclic accelerated capillary angle processing (ECAP) or multi-axis forging (MDF).
[0062] Specifically, the present invention provides the following production method. That is, (I) preparing a pure titanium material having a substantially cylindrical shape and a cross-sectional area of A0; and (II) swaging the pure titanium material; By having the above structure, a substantially cylindrical screw base material having a cross-sectional area of A1 after swaging and a true strain expressed as ln(A0 / A1) of 2 or more can be obtained. Also, (I) preparing a substantially cylindrical pure titanium material having a cross-sectional area of A0; and (II) swaging the pure titanium material; By having the above structure, a substantially cylindrical screw base material is obtained having a cross-sectional area of A1 after swaging and a degree of processing expressed by 100×{(A0-A1) / A0} of 86% or more.
[0063] Here, "true strain" is an index showing the degree of processing, and true strain ε can be expressed by the following equation 2 from the cross-sectional area A0 before processing and the cross-sectional area A1 after processing.
[0064]
number
[0065] Here, the "degree of processing" is literally an index showing the degree of processing, and the degree of processing e can be expressed by the following formula 3 from the cross-sectional area A0 before processing and the cross-sectional area A1 after processing.
[0066]
number
[0067] For example, when the degree of working e is 80%, the true strain ε is 1.61, when the degree of working e is 90%, the true strain ε is 2.3, and when the degree of working e is 95%, the true strain ε is 3.0. In the present invention, the true strain ε is 2 or more (degree of working 86% or more), preferably 2.5 or more (degree of working 92% or more), and more preferably 3 or more (degree of working 95% or more). The screw base material obtained by the method of the present invention has the same definition and characteristics as above.
[0068] The conditions of the swaging are not particularly limited as long as the above-mentioned true strain ε and / or the above-mentioned degree of working e can be achieved. For example, the swaging conditions may be set so that the surface temperature of the material being processed becomes 250° C. or higher, but are not limited thereto.
[0069] The present invention also provides a method for manufacturing a screw. That is, (III) a step of imparting a screw shape to the screw base material obtained by the above-mentioned method for producing a screw base material or to the screw base material having the above-mentioned properties; The present invention provides a method for producing a screw, which further comprises the steps of: In the above manufacturing method, the true strain and the degree of working have the same definitions as above. EXAMPLES
[0070] <Pure titanium material> As pure titanium materials, i) two types of pure titanium (CP-T2) with a wire diameter of 5.8 mm (manufactured by Toho Tech Co., Ltd.) and ii) four types of pure titanium (CP-T4) with a wire diameter of 6.0 mm (manufactured by Toho Tech Co., Ltd.) were prepared. In addition, iii) a block-shaped material (manufactured by Kawamoto Heavy Industries Co., Ltd.) was prepared in which the two types of pure titanium were subjected to ultrafine deformation processing (UFG) to refine the crystals to 1 μm or less, and this block-shaped material was machined to prepare a bar material with a wire diameter of 6.0 mm (FTi2).
[0071] These were subjected to swaging processing at room temperature several times using a 15HP-SD type (four-way) swaging machine manufactured by Yoshida Memorial Co., Ltd. The true strain in each swaging process was set to 0.15-0.25, and by performing this process several times, four or five types of rod-shaped processed base materials were prepared with true strains ranging from 0 to approximately 3.7 in total (approximately 97% degree of processing). In each swaging process, the surface temperature of the material was measured using a radiation thermometer, and the surface temperature, the rotation speed of the swager, the forward speed of the bar material, the application of lubricating oil per unit time, etc. were adjusted so that the surface temperature was 300 to 400° C. The strain rate was calculated from the above swager conditions.
[0072] <Crystallite size and orientation> To obtain the crystallite size and orientation, samples for X-ray diffraction were prepared by cutting each of the rod-shaped processed base materials on a plane perpendicular to the axial direction and embedding them in phenolic resin. The resin-embedded samples were wet-polished with SiC waterproof abrasive paper of sizes #400, #800, #1200, and #2400 in order of roughness so that the surface was exactly perpendicular to the axial direction of each base material, and then buffed with silicon dioxide suspension (OP-S) to give a mirror finish.
[0073] The crystallite size was measured using an X-ray diffractometer (D8 ADVANCE) manufactured by BRUKER, with cobalt Kα radiation at a cobalt tube output of 35 kV and a current of 40 mA. The X-ray scanning range was 2θ = 35.0° to 48.0°, the divergence slit diameter was 0.3 mm, and the collimator diameter was 0.3 mm. The measurement data was analyzed using BRUKER analysis software DIFFRAC.EVA.
[0074] The orientation was measured using an X-ray diffractometer (D8 ADVANCE) manufactured by BRUKER under the same conditions as above. The in-plane direction angle Φ of the sample was measured in 72 steps at 5 degree intervals over a 360 degree circumference, and the range of the tilt angle Ψ was measured with a starting point of 15 degrees and an end point of 45 degrees. The obtained measurement data was used to create pole figures for the (1 0 -1 0) plane using the analysis software DIFFRAC.TEXTURE MRDB V4.1 (manufactured by BRUKER). The pole figures are shown in Figure 1. The maximum value of the relative intensity, with the average intensity of the entire pole figure defined as 1, was taken as the maximum specific intensity. In Figure 1, when the material is isotropic, i.e., when there is no orientation, there is little color shading, but when orientation appears, a dark area appears at a certain angle, and the relative intensity at that angle becomes high.
[0075] For the obtained rod-shaped processed base material, the crystallite size and the axial orientation of the (1 0 -1 0) plane of pure titanium were determined under the above-mentioned conditions.
[0076] <Mechanical properties> The obtained rod-shaped processed base material was measured for mechanical properties such as tensile strength, Vickers hardness, and reduction in area. The tensile test was carried out using an Amsler universal testing machine. The hardness was measured using a micro Vickers hardness tester with a load of 2.94 N. The reduction in area (RA) was calculated by converting the diameter of the sample after fracture in the tensile test into area using Equation 4. In Equation 4, D0 is the diameter of the material before the test, and D1 is the diameter of the necked portion of the material after the tensile test.
[0077]
number
[0078] 2 to 4 are graphs in which the horizontal axis represents the crystallite size and the vertical axis represents the mechanical properties. Specifically, in FIG. 2, the horizontal axis represents crystallite size and the vertical axis represents tensile strength. FIG. 3 is a graph in which the horizontal axis represents crystallite size and the vertical axis represents hardness. Furthermore, in FIG. 4, the horizontal axis represents the crystallite size and the vertical axis represents the aperture. 2 to 4 show that when the base material has desired mechanical properties, such as a tensile strength of 800 MPa or more, a hardness of 200 HV or more, and a reduction in area of 45% or more, its crystallite size is 280 Å or less. Therefore, it can be seen that in pure titanium, a crystallite size of 280 Å or less ensures that the base material has the desired mechanical properties.
[0079] FIG. 5 is a graph in which the horizontal axis represents true strain and the vertical axis represents crystallite size. It can be seen from FIG. 5 that in order to achieve a crystallite size of 280 Å or less, it is preferable to set the true strain to 2 or more (a degree of working of 86% or more). 2 to 4, it can be seen that by setting the true strain to 2 or more (degree of processing to 86% or more), a base material having desired mechanical properties can be obtained.
[0080] FIG. 6 is a graph in which the horizontal axis represents true strain and the vertical axis represents maximum specific strength. It can be seen from FIG. 6 that in order to achieve a maximum specific strength of 3 or more, the true strain should be 2 or more. 7 to 9 are graphs in which the horizontal axis represents maximum specific strength and the vertical axis represents mechanical properties. Specifically, the vertical axis in FIG. 7 is tensile strength, the vertical axis in FIG. 8 is hardness, and the vertical axis in FIG. 9 is reduction in area. It can be seen from Figs. 7 to 9 that when the maximum specific strength is 3 or more, the desired mechanical properties are obtained, for example, a tensile strength of 800 MPa or more, a hardness of 200 HV or more, and a reduction in area of 45% or more.
[0081] FIG. 10 is a diagram showing the relationship between true strain (horizontal axis) and reduction in area of a base material obtained using material CP-T4. From Figure 10, we can see that the reduction in area increases with an increase in true strain. In particular, at a true strain of 3.5 (a degree of processing of 97%), the reduction in area increases to over 70%. This value corresponds to that of pure titanium type 2. Moreover, from FIG. 10, it can be seen that if the true strain is 2 or more, the reduction in area is 45% or more. From FIG. 10 and FIG. 5, it is understood that swaging should be performed so that the true strain is 2 or more (degree of processing 86% or more).
[0082] <Head moldability> Table 1 shows the head formability of the screw formed using the rod-shaped processed base material. Furthermore, the screw could be formed from the rod-shaped processed base material by upsetting (forging) in the same way as in normal screw forming. From Table 1, it can be seen that when using ii) CP-T4 as the raw material and the rod-shaped processed base material obtained with a true strain of 2.65 or more (degree of processing 93%), the forging process of the head, which is usually carried out at a true strain of around 0 (degree of processing 0%) and at 400°C or more, can be carried out at a lower temperature of 200°C.
[0083] [Table 1]
[0084] Conventionally, medical screws made from pure titanium type 4, which has a high oxygen content among pure titanium materials, have high material strength but poor plastic workability, and it has been difficult to forge medical screws at temperatures below 200°C, so the screw heads have been formed by hot working (above 400°C) or cutting. Processing in these temperature ranges requires solid lubrication, which significantly reduces productivity. To reduce costs and improve productivity, there has been a demand for the same material with the plastic workability (especially drawing) that allows for forging at temperatures below 250°C. However, as can be seen from Table 1, the present invention makes it possible to process the head by forging even at temperatures below 250°C.
[0085] Figure 11 shows a photograph of the head of CP-T4 when the recess in the head is machined into a hexalobular shape. When CP-T4 was used without machining (true strain 0, degree of machining 0%), cracks (ductile fracture) occurred in the head of the screw at 200°C, and head forming was not possible, as shown in A1, A2, and A3 in Figure 11. However, the rod-shaped machined base material obtained with ii) CP-T4 as the raw material and true strain 2 (degree of machining 86%) and true strain 2.65 (degree of machining 93%) could be machined normally without cracks.
Claims
1. A pure titanium screw base material or screw having a substantially cylindrical shape, the maximum specific intensity of the orientation of the (1 0 -1 0) plane in the axial direction of the substantially cylindrical shape being 3 or more, and the crystallite size of the pure titanium being 280 Å or less; A screw matrix or screw having at least one of the following characteristics i) to iii): Property i): Tensile strength of 800 MPa or more; Characteristic ii): hardness of 200 HV or more; Characteristic iii): Aperture is 45% or more.
2. A screw base material or screw as described in claim 1, wherein the maximum value of the specific strength is 5 or more.
3. 3. The screw base material or screw according to claim 1 or 2, wherein the pure titanium is selected from the group consisting of pure titanium type 2, pure titanium type 3, pure titanium type 4, and pure titanium whose crystal grains have been refined to 1 μm or less.
4. The screw base material or screw according to any one of claims 1 to 3, wherein the pure titanium is pure titanium type 4.
5. The screw base material or screw according to any one of claims 1 to 4, wherein the screw base material or screw is a medical anchor screw base material or a medical anchor screw.
6. The screw base material or screw according to any one of claims 1 to 5, wherein the screw base material or screw is an anchor screw base material for orthodontics or an anchor screw for orthodontics.